An Investigation on the Effect of Solvent and Heat to Clay Minerals in Shaly Sandstone - Wan Zairani Wan Bakar; Ismail Mohd Saaid; Mohd Riduan Ahmad; Husna Hayati Jarni; Siti Qurratu’ Aini Mahat (Indonesian Journal of Chemistry, 2020)
Core cleaning could be complicated for samples that contain a high amount of clays. Some clays are delicate and exposure to solvent and heat would damage or alter its properties. In this study, we investigated the effect of direct exposure of solvent and heat to clay mineral properties based on petrographical data from X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscope (FESEM) and Energy Dispersive X-Ray (EDX). Experiments were performed on sidewall core samples taken in a shaly sand zone. The FTIR data did not show any changes at the molecular level to the clay mineral after direct contact with the selected solvent. The FESEM images showed some illite floccules collapse in the samples exposed to oven-drying at 60 °C.